2005
DOI: 10.1097/01.jom.0000188332.10217.4b
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Pulmonary Function Change Over Time in the Occupational Setting

Abstract: Periodic spirometry testing is performed in medical screening and surveillance programs for workers with various occupational exposures and for cigarette smokers. The recent American College of Occupational and Environmental Medicine (ACOEM) evidence-based statement, Spirometry in the Occupational Setting, comprehensively reviewed the issues involved in conducting and interpreting standardized spirometry tests in occupational medicine. 1 However, interpreting change over time was only briefly discussed in that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Most data was collected before the Third National Health and Nutrition Examination Survey (NHANES III) based standards were recommended [Pellegrino et al, 2005;Townsend, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…Most data was collected before the Third National Health and Nutrition Examination Survey (NHANES III) based standards were recommended [Pellegrino et al, 2005;Townsend, 2005].…”
Section: Discussionmentioning
confidence: 99%
“…For occupational health care, it is desirable to identify employees having an increased risk of COPD, preferably before the disease is established (30). Guidelines for surveillance of workers with an increased risk of work-related obstructive respiratory disease are, however, lacking.…”
Section: Discussionmentioning
confidence: 98%
“…Guidelines for surveillance of workers with an increased risk of work-related obstructive respiratory disease are, however, lacking. The individual analyses of the measurements from repeated spirometries have several pitfalls (30,31). Moreover, repeated spirometries in large work forces where only a minority of the employees have an elevated risk of COPD is costly.…”
Section: Discussionmentioning
confidence: 99%
“…Because longitudinal interpretation typically requires a minimum of several years of data to estimate slope, the traditional cross-sectional approach was used for the first 4 years, whereupon time-variant improvement in the sensitivity and specificity was incorporated. Empirical studies 1,20,21 have shown that the pattern of technical improvement of test performance over Uhe ϭ utility healthy exposed; Ued ϭ utility early disease; Uie ϭ utility identified early; Uad ϭ utility advanced disease; Ufp ϭ utility false positive. time is statistically complex; we used a simple algorithm with improvement in sensitivity and specificity logarithmically related to the number of testing episodes to date (eg, at any screen, performance would be better with semiannual testing than with biannual testing).…”
Section: Interpretive Paradigm: Longitudinal Criteriamentioning
confidence: 99%